Respuesta :

Answer:

[tex]y = 1[/tex]

Step-by-step explanation:

Given

Attached graph

Required

The graph equation

Pick any two points, we have:

[tex](x_1,y_1) = (1,1)[/tex]

[tex](x_2,y_2) = (3,1)[/tex]

Calculate slope (m)

[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]

[tex]m = \frac{1 - 1}{3 - 1}[/tex]

[tex]m = \frac{0}{2}[/tex]

[tex]m = 0[/tex]

The equation is then calculated using:

[tex]y = m(x - x_1) + y_1[/tex]

This gives:

[tex]y = 0* (x - x_1) + 1[/tex]

[tex]y = 1[/tex]

Hence, the equation is:

[tex]y = 1[/tex]